Multiscale viscoplastic modeling of recycled glass fiber-reinforced thermoplastic composites: Experimental and numerical investigations. (1st August 2022) - Nachtane, M.; Meraghni, F.; Chatzigeorgiou, G.; Harper, L.T.; Pelascini, F.
Abstract: One of the main challenges facing fiber-reinforced polymer composites is the lack of options for end-of-life recycling. The environmental impact of waste materials disposed of at landfill sites, by incineration, or by erratic dispersion in the environment is accelerating the need to find innovative solutions to increase the value of recycled materials. This research aims to investigate the relationship between microstructural parameters and the mechanical properties of a recycled thermoplastic composite material. The latter is processed by thermocompression molding of a polyamide (PA66) matrix reinforced with chopped glass strands. An innovative approach is proposed to link the local microstructure of the composite to the mechanical behavior of the recycled material. It exploits an experimental characterization of the material microstructure using optical microscopy and X-ray micro-computed tomography (mCT). The experimental findings are implemented into a numerical modeling strategy to mimic the flexural behavior, based on a micromechanical approach coupling mean and full-field analysis. The region of interest is reconstructed from detailed 3D images using a modified random sequential adsorption (MRSA) algorithm, while other regions are modeled as homogenized macro-scale continua. Furthermore, the abilities of the proposed approach are proven by incorporating the viscoplastic behavior of the random heterogeneous material induced by the polymer matrix. The originality of the present research consists of the multi-scale FE analysis and the experimental validation for the viscoplastic behavior of the recycled composite material, taking into account influences from the microstructure. Graphical abstract: Comparison between experimental data from three-point flexural test and numerical results predicted using the developed multi-scale modeling strategy for TP-ROS composite accounting for viscoplastic regime of the PA66 matrix. Image 1